Strength group of Engkabang jantong as fast-growing indigenous species timber in Sarawak - Gaddafi, Ismaili; Khairul Khuzaimah, Abdul Rahim; Zurina, Ismaili (UNIV LAGOS, 2016)
Engkabang jantong is one of fast-growing indigenous species of Sarawak. Due to shortage of the source for heavy hardwood in the timber industries, an effort had been carried out to identify alternative species. Small clear sample is the most suitable for strength properties test. This paper aimed to acquire the strength group of fastgrowing indigenous of Engkabang jantong compared with Acacia mangium as reference point. Strength properties at green and dry conditions are required namely bending parallel to grain, compression stress parallel to grain, shear parallel to grain and modulus of elasticity. The MS 544: Part 2 (2001) was used for strength group identification by converting the ultimate stresses